1,3-Dipolar cycloaddition reaction of D-glucose-derived nitrone with allyl alcohol: synthesis of 2-hydroxy-1-deoxycastanospermine analogues - Karanjule, Narayan S.; Markad, Shankar D.; Sharma, T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2005)
The synthesis and evaluation of glycosidase inhibitory activity of polyhydroxylated indolizidine alkaloids namely 2-hydroxy-1-deoxycastanospermine 3a,b and 2-hydroxy-1-deoxy-8a-epi-castanospermine 3c,d is reported. The key step involves the intermolecular 1,3-dipolar cycloaddition of allyl alcohol to D-glucose-derived nitrone 4, followed by tosylation, that afforded four diastereomeric sugar-substituted isoxazolidines 5a-d with the desired regioselectivity. The one-pot conversion of 5a-d to pyrrolidines 8a-d by hydrogenolysis, removal of 1,2-acetonoide functionality, and hydrogenation afforded corresponding target molecules 3a-d.

2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

6(2,4-Dichlorophenoxy)dibenzo[d,f][1,3,2]dioxa-phosphepine-6-sulfide - Krishnaiah, M.; Babu, V. H. H. Surendra; Krishna, J. R.; Kumar, K. A.; Reddy, C. S.; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2005)
In the title compound, C18H11Cl2O3PS, the seven-membered phosphepine ring exhibits a distorted-boat conformation, with the phosphoryl sulfide group axial and the dichlorophenoxy group equatorial. Fusion of the phosphepine ring to the biphenyl system causes strain, as evidenced by both widening and compression of the endocyclic angles in the heterocyclic ring. The P=S bond length is 1.8939 (12) angstrom and the planar dichlorophenyl ring is oriented at an angle of 28.70 (6)degrees to the phosphepine ring.

Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

Chiral 2-C-methylene glycosides and carbohydrate-derived pyrano[2,3-b][1]benzopyrans: synthesis via InCl3 catalyzed stereoselective ferrier rearrangement of 2-C-acetoxymethyl glycal derivatives - Ghosh, R.; Chakraborty, A.; Maiti, D. K.; Puranik, Vedavati G. (Tetrahedron Letters, 2005)
2-C-Acetoxymethyl glycal derivatives react with aliphatic alcohols in the presence of InCl3 (30 mol %) to furnish the corresponding 2-C-methylene glycosides in excellent yields and with exclusive alpha-selectivity except for the methyl 2-C-methylene glycosides, which are formed in similar to 2:1 anomeric ratio in favour of the alpha-anomer. The reaction of 2-C-acetoxyglycals with phenols, however, produces the corresponding chiral carbohydrate-derived pyranobenzopyran derivatives via initial Ferrier rearrangement followed by tandem cyclization in excellent yields and moderate to high stereoselectivities in favour of the corresponding 10a-R-pyrano[2,3-b][1]benzopyran derivatives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 2-C-methylene glycoside; InCl3; pyranobenzopyran; Stereoselective

DNA-binding studies of mixed ligand cobalt(III) complexes - Barve, A. C.; Ghosh, Smita; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G. (Transition Metal Chemistry, 2005)
The DNA binding characteristics of mixed ligand complexes of the type [Co(en)(2)(L)]Br-3 where en = N,N'-ethylenediamine and L = 1,10-phenanthroline (phen), 2,2'-bipyridine (bpy), 1,10-phenanthroline-5,6-dione (phendione), dipyrido[3,2-a:2',3'-c]phenazine (dppz) have been investigated by absorption titration, competitive binding fluorescence spectroscopy and viscosity measurements. The order of intercalative ability of the coordinated ligands is dppz > phen > phendione > bpy in this series of complexes.

(E)-1-(2-Hydroxy-3,4-dimethoxyphenyl)-3-(4-hydroxyphenyl)-prop-2-en-1-on e - Krishna, J. R.; Kumar, N. J.; Krishnaiah, M.; Rao, C. V.; Rao, Y. K.; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2005)
The title compound, C17H16O5, crystallizes with two independent molecules in the asymmetric unit. These are oriented approximately orthogonal to one another. The keto group adopts an s-cis conformation; the six-membered ring formed by the O-H&BULL;&BULL;&BULL; O hydrogen bond and the adjacent benzene ring are approximately coplanar. In addition to an intramolecular O-H&BULL;&BULL;&BULL; O hydrogen bond, intermolecular O-H&BULL;&BULL;&BULL; O interactions link adjacent molecules into chains.

Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Larvicidal activity of acacia nilotica extracts and isolation of D-pinitol - a bioactive carbohydrate - Chaubal, Rohini; Pawar, P. V.; Hebbalkar, G. D.; Tungikar, V. B.; Puranik, Vedavati G.; Deshpande, V. H.; Deshpande, N. R. (Chemistry & Biodiversity, 2005)
A low-molecular-weight, sugar-like compound other than glucose, fructose, sucrose, or myo-inositol showing lipophilic nature was isolated from the EtOH extract of Acacia nilotica. The structure of the compound was determined by spectral methods. This alicyclic polyalcohol was found to be D-pinitol (- 3-O-methyl-D-chiro-inositol; 1). The configuration of the compound was confirmed by single-crystal X-ray analysis. The compound I is known from Soybean, Australian mangroves, Fagonia indica, A rachis hypogaea, etc., but we have isolated this compound for the first time from the aerial parts of A. nilotica. Very few references have been cited for compound I for its entomological activity, and there are no reports on mosquitoes. Therefore, the crude extracts of A. nilotica were tested for its biological activity against mosquito larvae. Acetone extract at 500-ppm concentration showed chronic toxicity against Aedes aegypti and Culex quinquefasciatus IVth instar mosquito larvae. Such a biological activity has been observed for the first time for this plant. This study could be a stepping stone to a solution for destroying larval species as well as consumption of such a widely grown, problem weed, A. nilotica. This larvicidal agent, since it is derived from plant, is eco-friendly, cost effective, non-hazardous to nontarget organisms and would be safe unlike commercially available insecticides.

Preorganizing linear (self-complementary) quadruple hydrogen-bonding arrays using intramolecular hydrogen bonding as the sole force - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2005)
In this article we describe a rational approach for prefixing multiple cooperative binding sites in an ideal spatial arrangement on a structurally rigid backbone, constrained exclusively by intramolecular hydrogen bonding. The idea is exemplified by the ability of the self-assembling constructs la-e and 2a,b to form hydrogen-bonded dimers, whose structural preorganization has been solely effected by intramolecular hydrogen bonding. The readily accessible amidinourea backbone has been used as a common platform for the construction of a variety of such self-assembling systems. ESI mass spectrometry and single-crystal X-ray diffraction studies have been particularly effective in investigating the self-assembling propensities of these systems. Remarkably, most the H-bonded dimers reported herein undergo an unusual mode of self-assembly, using intermolecular four-membered ring hydrogen-bonded interaction, affording extended supramolecular networks.

Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Stereospecific route to 5,11-methanomorphanthridine alkaloids via intramolecular 1,3-dipolar cycloaddition of nonstabilized azomethine ylide: Formal total synthesis of (+/-)-pancracine - Pandey, Ganesh; Banerjee, Prabal; Kumar, Ravindra; Puranik, Vedavati G. (Organic Letters, 2005)
[GRAPHICS] The core structure of the complex pentacyclic 5,11-methanomorphanthridine alkaloids is constructed stereospecifically in one step employing an intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The strategy is demonstrated by accomplishing the formal total synthesis of (+/-)-pancracine.

Synthesis and characterization of ferrocenylchalcogenopropargyl complexes [Fe(eta(5)-(C5H4ECH2C)-C-I CH)(2)] (E-I = Se, S) and their reactions to form unusual ferrocenyl-containing metal clusters with eclipsed Cp rings and new five-membered (FeECH)-C-I = - Mathur, P.; Singh, V. K.; Mobin, Shaikh M.; Srinivasu, C.; Trivedi, R.; Bhunia, A. K.; Puranik, Vedavati G. (Organometallics, 2005)
{The new bis(chalcogenopropargyl)ferrocene complexes [Fe(eta(5)-C(5)H(4)E(I)CH(2)CdropCH)(2)] (E-I = Se, 1; E-I = S, 2) have been prepared by treatment of the dilithiated [Fe(eta(5)-C5H4Li)(2)] with Se or S powder, followed by reaction with propargyl bromide. Reaction of 1 and 2 with [Fe2M(mu(3)-E)(2)(CO)(9)] (E = S, Se and M = Fe, Ru) forms new clusters which feature an unusual five-membered (FeECH)-C-I=CCH2 ring with a pi bond between the olefinic unit and the Fe atom, and the Cp rings adopt an eclipsed arrangement. The structures of 1 and [Fe(eta(5)-C5H4E(I)-CH(2)CdropCH) (eta(5)-C5H4{Fe2M(CO)(8)(mu-E)((ECHCCH2)-C-I)})] (M = Fe

Synthesis of cis bis-beta-lactams via Staudinger cycloaddition reaction using C-2-symmetric 1,2-diamines - Shaikh, A. L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2005)
An efficient stereoselective synthesis of bis-beta-lactams via cycloaddition reaction (Staudinger reaction) of ketenes with bisimines derived from C-2-symmetric 1, 2-diamines is described. The reaction provided diastereomeric mixture of meso and C-2-symmetric cis-bis-beta-lactams with higher selectivity for meso-bis-beta-lactams. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; Staudinger cyclo-addition reaction; stereoselective synthesis

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Unusual monodentate binding mode of 2,2 `-dipyridylamine (L) in isomeric trans(acac)(2)Ru-II(L)2, trans-[(acac)(2)Ru-III(L)(2)]ClO4, and cis-(acac)(2)Ru-II(L)(2) (acac = acetylacetonate). Synthesis, structures, and spectroscopic, electrochemical, and magn - Kar, S.; Chanda, N.; Mobin, Shaikh M.; Urbanos, F. A.; Niemeyer, M.; Puranik, Vedavati G.; Jimenez-Aparicio, Reyes; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
{The reaction of cis-Ru(acac)(2)(CH3CN)(2) (acac = acetylacetonate) with 2,2'-dipyridylamine (L) in ethanolic medium resulted in facile one-pot synthesis of stable [(acac)(2)Ru-III(L)]ClO4 ([1]ClO4), trans-[(acac)(2)Ru-II(L)2] (2), trans[(acac)(2)Ru-III(L)(2)[ClO4 ([2]ClO4), and cis-[(acac)(2)Ru-II(L)(2)] (3). The bivalent congener 1 was generated via electrochemical reduction Of [1]ClO4. Although in [1](+) the dipyridylamine ligand (L) is bonded to the metal ion in usual bidentate fashion, in 2/[2](+) and 3, the unusual monodentate binding mode of L has been preferentially stabilized. Moreover, in 2/[2](+) and 3, two such monodentate L's have been oriented in the trans- and cis-configurations, respectively. The binding mode of L and the isomeric geometries of the complexes were established by their single-crystal X-ray structures. The redox stability of the Ru(II) state follows the order 1 < 2 much less than 3. In contrast to the magnetic moment obtained for [1]ClO4

2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz)-derived [Ru-II(tptz)(acac)(CH3CN)](+) and mixed-valent [(acac)(2)Ru-III(mu-tptz-H+)(-)Ru-II(acac)(CH3CN)](+) - Ghumaan, Sandeep; Kar, S.; Mobin, Shaikh M.; Harish, B.; Puranik, Vedavati G.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
Mononuclear [Ru-II(tptz)(acac:)(CH3CN)]ClO4 ((ClO4)-Cl-[1]) and mixed-valent dinuclear [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(CH3CN)]ClO4 ([5]ClO4; acac = acetylacetonate) complexes have been synthesized via the reactions of Ru-II(acac)2(CH3CN)(2) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz), in 1:1 and 2:1 molar ratios, respectively. In [1]ClO4, tptz binds with the Ru-II ion in a tridentate N,N,N mode (motif A), whereas in [5]ClO4, tptz: bridges the metal ions unsymmetrically via the tridentate neutral N,N,N mode with the Ru-II center and cyclometalated N,C- state with the Ru-III site (motif F). The activation of the coordinated nitrile function in [1]ClO4 and [5]ClO4 in the presence of ethanol and alkylamine leads to the formation of iminoester ([2]ClO4 and [7]ClO4) and amidine ([4]ClO4) derivatives, respectively. Crystal structure analysis of [2]ClO4 reveals the formation of a beautiful eight-membered water cluster having a chair conformation. The cluster is H-bonded to the pendant pyridyl ring N of tptz and also with the O atom of the perchlorate ion, which, in turn, makes short (C-H––-O) contacts with the neighboring molecule, leading to a H-bonding network. The redox potentials corresponding to the (RuI)-I-I state in both the mononuclear {[(acac)(tptz)Ru-II-N=-C-CH3]ClO4 ([1]ClO4) >> [(acac)(tptz)Ru-II-NH=C(CH3)-OC2H5]ClO4 ([2]ClO4) > [(acac)(tptz)(RuNH2)-N-II-C6H4(CH3)]ClO4 ([3]ClO4) > [(acac)(tptz)Ru-II-NH=C(CH3)-NHC2H5]ClO4 ([4]ClO4)} and dinuclear {[(acac)(2)Ru-III-{mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 {(mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 ([5]ClO4), [(acac)(2)Ru-III[(mu-tptz-H+(N-O ([6]ClO4), [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NH=C(CH3)-OC2H5)]ClO4( [7]ClO4), and [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NC4H4N)]ClO4 ([8]ClO4), complexes vary systematically depending on the electronic nature of the coordinated sixth ligands. However, potentials involving the Ru-III center in the dinuclear complexes remain more or less invariant. The mixed-valent (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) exhibits high comproportionation constant (K-c) values of 1.1 X 10(12)-2 x 109, with substantial contribution from the donor center asymmetry at the two metal sites. Complexes display Ru-II- and Ru-III-based metal-to-ligand and ligand-to-metal charge-transfer transitions, respectively, in the visible region and ligand-based transitions in the UV region. In spite of reasonably high K, values for [5]ClO4[8]ClO4, the expected intervalence charge-transfer transitions did not resolve in the tpical near-IR region up to 2000 nm. The paramagnetic (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) displays rhombic electron paramagnetic resonance (EPR) spectra at 77 K (< g > similar to 2.15 and Delta g similar to 0.5), typical of a low-spin Ru-III ion in a distorted octahedral environment. The one-electron-reduced tptz complexes [RuII(tptz center dot-)(acac)(CH3CN)] (1) and [(acac)(2)Ru-III{mu-tptz-H+)(center dot 2-)}-Ru-II(acac)(CH3CN)] (5), however, show a free-radical-type EPR signal near g = 2.0 with partial metal contribution.

3-(2,4-Dichlorophenyl)-1-(4-methoxyphenyl)prop-2-en-1-one - Rosli, Mohd Mustaqim; Patil, P. S.; Fun, Hoong-Kun; Razak, Ibrahim Abdul; Puranik, Vedavati G.; Dharmaprakash, S. M. (Acta Crystallographica Section E-Structure Reports Online, 2006)
In the title compound, C16H12Cl2O2, the dihedral angle between the benzene rings is 28.63 (6)degrees. The crystal structure is stabilized by intermolecular C-H center dot center dot center dot O hydrogen bonds and by short Cl center dot center dot center dot Cl interactions.

3-(3-bromophenyl)-1-(4-methoxyphenyl)-prop-2-en-1-one - Patil, P. S.; Rosli, Mohd Mustaqim; Fun, Hoong-Kun; Razak, Ibrahim Abdul; Puranik, Vedavati G.; Dharmaprakash, S. M. (Acta Crystallographica Section E-Structure Reports Online, 2006)
In the title compound, C16H13BrO2, the dihedral angle between the aromatic rings is 41.34 (6)degrees. The molecules (via two C-H center dot center dot center dot O intermolecular interactions) form chains along the a axis that stack into layers parallel to the b axis.

Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules

Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids

Facile synthesis of 1,3,7-trihydroxyxanthone and its regioselective coupling reactions with prenal: simple and efficient access to osajaxanthone and nigrolineaxanthone F - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2006)
A facile five-step synthesis of naturally occurring 1,3,7-trihydroxyxanthone has been described starting from 1,3,5-trimethoxybenzene via NBS-induced nuclear bromination, lithiation followed by an in situ benzoylation with methyl 2,5-dibenzyloxybenzoate, selective deprotection of the two benzyl groups, base-catalyzed intramolecular cyclization, and demethylations pathway with 62% overall yield. The regioselective coupling reactions of 1,3,7-trihydroxyxanthone with prenal in the presence of calcium hydroxide at room temperature and under thermal conditions at 140-150 degrees C have been demonstrated to exclusively obtain the natural products osajaxanthone in 75% yield and nigrolineaxanthone F in 98% yield, respectively.

Gamma-heteroatom directed stereocontrolled staudinger cycloaddition reaction of vinylketenes and imines - Shaikh, Aarif L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron Letters, 2006)
Vinylketenes possessing a gamma-heteroatom, on Staudinger cycloaddition reaction with imines gave trans-3-vinyl-beta-lactams in very good yields. The vinyl side chain stereoselectively adopts the Z-configuration in the transition state to stabilize the vinylketene and produces, exclusively, trans-3-vinyl-beta-lactams. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: imines; Staudinger reaction; stereoselective synthesis; vinylketenes

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Supramolecular self-assembled ruthenium-polypyridyl framework encapsulating discrete water cluster - Deshpande, Megha S.; Kumbhar, A. S.; Puranik, Vedavati G.; Selvaraj, K. (Crystal Growth & Design, 2006)
Keywords: 4; 4 `-dimethoxydiphenylmethane; benzylsulfonic acid; Condensation of anisole; p-formaldehyde; Zr-TMS-BSA

Synthesis, characterization, X-ray structure and DNA photocleavage by cis-dichloro bis(diimine) Co(III) complexes - Ghosh, Smita; Barve, A. C.; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G.; Datar, P. A.; Sonawane, U. B.; Joshi, Rohini R. (Journal of Inorganic Biochemistry, 2006)
Keywords: Acetic acid; acrylic acid; oxidative conversion of propane; rare earth-doped Mo-V-Sb catalysts

Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Total synthesis of (-)-radicamine B - Gurjar, Mukund K.; Borhade, Ramdas G.; Puranik, Vedavati G.; Ramana, C. V. (Tetrahedron Letters, 2006)
The synthesis of a chiral cyclic nitrone with L-arabino configuration and its application in the total synthesis of radicamine B is reported. An agreement in the spectral data with natural radicamine B but specific rotation with an opposite sign warranted a revision of the absolute configuration of radicamine B. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: codonopsinine; Cyclic nitrone; Grignard addition; polyhydroxy pyrrolidine alkaloids; radicamine B

Towards the total synthesis of clavosolide A - Yakambram, Pedduri; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The synthesis of the monomeric unit of clavosolide A from 1,2:5,6-di-O-isopropylidene-alpha-D-glucose is presented. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: clavosolide A; diolide; reductive oxirane opening; seco acid; Simmons-Smith cyclopropanation

3-(3-Methylphenoxy)-1,5-dihydro-2,4,3-benzodioxaphosphepin-3-one - Krishna, J. Radha; Krishnaiah, M.; Babu, M. F. Stephen; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2007)
In the title compound, C15H15O4P, the seven-membered phosphepine ring exhibits a twist-chair conformation, with the phosphoryl O atom in an equatorial and the methylphenoxy group in an axial position. The crystal structure is stabilized by both intra- and intermolecular C-H center dot center dot center dot O hydrogen bonds.

6-Bromo-3-(4-chlorophenyl)-2-(4-methoxyphenyl)-3,4-dihydro-1,3,2-benzoxa zaphosphinine 2-sulfide - Krishna, J. Radha; Krishnaiah, M.; Prasad, G. Syam; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2007)
In the title compound, C20H16BrClNO2PS, the six-membered oxazaphosphinine ring exhibits a boat conformation, with the S atom in an axial position. The methoxyphenyl and chlorobenzene groups are trans to each othe. The structure is stabilized by intermolecular C-H center dot center dot center dot S hydrogen bonds, linking the molecules into chains.

Carbohydrate based approach towards the synthesis of aspercyclide C - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A formal total synthesis of aspercyclide C (3) is described in which D-ribose is employed as a chiral pool material. The key step is a ring closing metathesis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: chiron approach; D-ribose; Mukaiyama reagent; ring closing metathesis (RCM); Ullmann coupling

Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.

Facile phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2+2] annulation reactions: an easy access to complex bioactive natural and unnatural benzopyran congeners - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
The complex bioactive natural and unnatural benzopyran congeners have been synthesized using one-/two-step approaches in very good yields from the reactions of two different dihydroxyphthalides, natural resorcyclic acid derivative, and trihydroxybenzophenone with citral and/or farnesal, via the phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions and three different thermal intramolecular cyclization reactions. The effects of the nature and the position of phenolic groups in the starting materials on the course of these cycloaddition reactions have also been described. Depending upon the absence or presence of intramolecular hydrogen bonding of the phenolic group with the carbonyl moiety in the starting materials, these phenol-driven intramolecular thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions either furnished the kinetically controlled products or directly formed the thermodynamically controlled rearranged products, respectively.

Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Rh(II)-catalyzed intramolecular N-H insertion of D-glucose-derived delta-amino alpha-diazo beta-ketoester: Synthesis of pyrrolidine iminosugars - Vyavahare, Vinod P.; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2007)
The rhodium acetate catalyzed reaction of D-glucose-derived delta-amino alpha-diazo beta-ketoester allows a stereoselective beta-facial intramolecular N-H insertion reaction that leads to formation of the bicyclic pyrrolidinone ring skeleton in high yield. The sugar-substituted pyrrolidinone thus obtained was elaborated to allow the synthesis of promising glycosidase inhibitors, namely, 2,5-dideoxy2,5-imino-L-glycero-alpha-D-galactoheptitol and 2,5-dideoxy-2,5-imino-D-galactitol.
Keywords: alkaloids; azasugars; carbohydrates; N-H insertion; Pyrrolidines; rhodium carbenoid

Stereoselective synthesis of spiro-beta-lactams using D-(+)-glucose derived chiral pool: remarkable influence of the torquoelectronic effect - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2007)
Diastereoselective synthesis of spiro-beta-lactams via [2+2] cycloaddition reaction of imines and chiral ketenes is described. The chiral ketene was prepared from commercially available, inexpensive D-glucose. Although, theoretically four diastereomers are possible, the reaction yielded only two diastereomers stereoselectively in good to moderate yields. The stereochemical outcome of the reaction was in accordance with the torquoelectronic model. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; spiro-beta-lactams; Staudinger reaction; stereoselective synthesis

Synthesis and glycosidase inhibitory studies of pentahydroxyindolizidines: D-Glucose-Derived aziridine-2-carboxylate approach - Kumar, K. S. Ajish; Chaudhari, Vinod D.; Puranik, Vedavati G.; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2007)
D-Glucose -derived aziridine-2-carboxylate I was converted into a-amino aldehyde 7, which, after Wittig olefination, asymmetric dihydroxylation, hydrogenation followed by LiAlH4 reduction, and N-Cbz protection, afforded two diastereomeric pyrrolidines 11a and 11b with sugar appendages. Removal of the 1,2-acetonide functionality in 11a/11b and reductive animation gave the pentahydroxyindolizidine alkaloids 6g and 6h, respectively, with (S) absolute configurations at the ring junctions. The glycosidase inhibitory activities of these compounds were studied.
Keywords: asymmetric dihydroxylation (AD); Iminosugars; indolizidine; N-methylmorpholine; N-oxide (NNIO)

Synthesis, NMR, X-ray crystallography and bioactivity of some alpha-aminophosphonates - Prasad, Gandavaram Syam; Krishna, Jadaprolu Radha; Manjunath, Manubolu; Reddy, Obulam Vijaya Sarathi; Krishnaiah, Musali; Reddy, Cirandur Suresh; Puranik, Vedavati G. (Arkivoc, 2007)
The synthesis of some new alpha-aminophosphonates (4a-l) was accomplished by one pot reaction of equimolar quantities of 2-amino-4-chlorophenol (1), various aromatic aldehydes (2a-l) and diethylphosphite (3) in dry toluene at reflux temperature. Products 4a-l were characterized by IR, H-1, C-13, P-31 NMR and in the case of 4g by X-ray crystal diffraction data.
Keywords: alpha-Aminophosphonates; Antibacterial

Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.

Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed

Unprecedented two-dimensional polymeric [Zn(OOC-C6H4-COO)(2)](2_)(n)[+H3N-(CH2)(3)-NH(3])(+)n system bearing one-dimensional chain of zinc(II) bis(phthalate) dianions held by propane-1,3-diammonium cations: crystal structure, thermal and fluorescent pr - Padmanabhan, A.; Joseph, K. C.; Puranik, Vedavati G.; Huang, Xiaoying; Li, Jing (Solid State Sciences, 2007)
A novel zinc(II) phthalate compound, [Zn{C6H4(COO)(2)}(2)](n)(2-)[NH3-(CH2)(3)-NH3](n)(2+), 1 Which contains four different phthalate moieties coordinated to the Zn(II) ion through one each of their carboxyl ate moieties in a eta(1)-form and each phthalate moiety acting as a bridging unit with an overall tetrahedral geometry around the metal ion has been prepared and structurally characterized. The structure is unique in the sense that the dianionic moieties [Zn{C6H4(COO)(2)}(2)](2-) form an infinite one-dimensional network composed of 14-membered cyclic units interconnected in a way that they are disposed alternatively in almost perpendicular planes. The dicationic [NH3-(CH2)(3)-NH3](2+) units are seen to hold these one-dimensional chains by strong coulombic and hydrogen bond interaction, resulting in an infinite two-dimensional layered structure of 1. The compound is thermally stable up to 250 degrees C. Above this temperature it loses one equivalent of phthalate moiety along with the diammonium unit to yield Zn(II) phthalate. The thermodynamic and kinetic parameters associated with this process could be evaluated using Coats-Redfern equation which shows the activation energy Ea for the process as 305.0 kJ mol(-1), the frequency factor A as 1.49 x 10(11) s(-1) and the entropy change Delta S as -35.90 JK(-1) mol(-1). Fluorescent emission properties of 1 was studied by exciting the compound at 380 nm and also at 322 nm which were found to be the two lambda(max) corresponding to absorptions of the molecule. Interestingly, the compound gave same type of emission spectra showing a maximum around 444 nm on exciting at these two different wavelengths, indicating that the molecule comes to the first excited state from the higher excited state by a fast non-radiative process before it exhibits singlet emission to come to the ground state. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 3-diammonium; cyclic chain; fluorescent emission; layered structure; propane; zinc(II) bis(phthalate) dianion; zinc-phthatate

Unusual trisulphide linkage in bromine-thiourea reaction: crystal structure of formamidinium trisulphide complex with bromine - Tol, Abhaya D.; Natu, Arun D.; Puranik, Vedavati G. (Molecular Crystals and Liquid Crystals, 2007)
{A new complex of formamidinium trisulphide with bromine has been synthesized. Single-crystal X-ray analysis of this compound revealed a novel trisulphide linkage in the formamidinium trisulphide moiety. The crystals belong to orthorhombic space group Fdd2 with a = 14.9119(15)
Keywords: bromine; crystal structure; formamidinium trisulphide; thiourea

C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Convenient access to 1, 3,4-trisubstituted pyrazoles carrying 5-nitrothiophene moiety via 1,3-dipolar cycloaddition of sydnones with acetylenic ketones and their antimicrobial evaluation - Rai, N. Satheesha; Kalluraya, Balakrishna; Lingappa, B.; Shenoy, Shaliny; Puranik, Vedavati G. (European Journal of Medicinal Chemistry, 2008)
Novel 1-aryl-3-(5-nitro-2-thienyl)-4-aroyl-pyrazoles 7 have been synthesized by the 1,3-dipolar cycloaddition of 3-arylsydnones 3 with 1-aryl-3-(5-nitro-2-thienyl)-2-propyn- 1-ones 6. The newly synthesized compounds were well characterized by elemental analysis, IR, (1)H NMR and mass spectral studies. They were also screened for their antibacterial and antifungal activities against a variety of microorganisms and the results of such studies have been discussed in this article. (c) 2007 Elsevier Masson SAS. All fights reserved.
Keywords: 1; 3-dipolar cycloaddition; 5-nitrothiophene; acetylenic ketone; Antibacterial; antifungal; Pyrazole; sydnone

Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

Hydrogen bonding-directed metallosupramolecular structural motifs based on a peripheral urea fused bipyridine tecton - Deshpande, Megha S.; Kumbhar, Avinash S.; Puranik, Vedavati G. (Crystal Growth & Design, 2008)
The potential of bipyridine glycoluril (BPG), a urea fused bipyridine, tecton to form metal-organic frameworks (MOFs) has been explored by structural characterization of BPG and its complexes [Ru(phen)(BPG)(2)]Cl(2) (1) and [Ru(BPG)(3)]Cl(2) (2). The single crystal X-ray structure of BPG reveals that the inherent H-bond donor (N-H) and acceptor groups (C=O) exhibit a potential to generate diverse supramolecular motifs depending on the stoichiometry of tectons. The single crystal X-ray analysis of the secondary building units 1 and 2 provide evidence for this hydrogen-bonding capacity which results in supramolecular self-assembled metal-organic frameworks (MOF) via C-H center dot center dot center dot Cl, C-H.center dot center dot center dot O, N-H center dot center dot center dot Cl, and N-H center dot center dot center dot O interactions with a cluster of water molecules and chlorine anions surrounding secondary building units in I and channels encapsulating mixed water-dimethylsulfoxide clusters in 2.

Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Synthesis of 1,2,3-triazole and 1,2,3,4-tetrazole-fused glycosides and nucleosides by an intramolecular 1,3-dipolar cycloaddition reaction - Anegundi, Ramakrishna I.; Puranik, Vedavati G.; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2008)
Various 1,2,3-triazole and 1,2,3,4-tetrazole fused multi-cyclic compounds were synthesized from carbohydrate derived azido-alkyne and azido-cyanide substrates. The acid sensitive 1,2-O-isopropylidene group of the furanosyl sugar was utilized for diversification to glycosides and nucleosides under Fischer glycosidation and Vorbruggen's conditions, respectively.

Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol

Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

Synthesis, structure and reactivity of azosalophen complexes of palladium - Pattanayak, Poulami; Pratihar, Jahar Lal; Patra, Debprasad; Puranik, Vedavati G.; Chattopadhyay, Surajit (Polyhedron, 2008)
The ligands 2-(arylazo)-1-N-salicylidene phenylamine, H(2)L(sal), (where H represents the dissociable protons upon complexation) afford stable orthopalladated complexes, [(L(sal))Pd], upon treatment with Na(2)[PdCl(4)]. The dinegative anionic (L(sal))(2-) ligands bind Pd(II) in a tetradentate (C, N, N, O) fashion with a distorted square planar geometry. The newly synthesized palladium complexes underwent oxygen insertion into the Pd-C bond with mCPBA (m-chloroperbenzoic acid) or TBHP (terbutylhydroperoxide)/[VO(acac)(2)] leading to the formation of stable azosalophen complexes of Pd(II) with the (O, N, N, O) coordination mode of the oxygenated ligand. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-(arylazo)-1-N-salicylidene phenylamine; azosalophen complex; orthopalladation; oxygen insertion

Tetranuclear manganese (III) salicylaldoxime ensemble - Kumbhar, Avinash S.; Mulay, Mahesh P.; Padhye, Subhash B.; Tavale, Sudam S.; Puranik, Vedavati G. (Structural Chemistry, 2008)
Crystal structure of {[Mn(salicylaldoximeH)(salicylaldoxime)](4)} center dot 3CHCl(3) 1 formed by the interaction of MnCl2 center dot 4H(2)O and salicylaldoxime in a 1:1 ratio is described. The compound crystallizes in the orthorhombic space group Pbca (No 61) with the lattice parameters; a = 27.769 (3), b = 22.672 (2), c = 21.650 (2) angstrom, V = 13630 (2) angstrom(3), Z = 8, R-1 = 0.0776, wR(2) = 0.2356, S = 1.164. The cluster with four Mn (III) centers formed by four terminal and four bridging salicylaldoxime ligands results in a central rotating wheel-like core with the Mn-Mn separation varying from 3.531 to 3.576 angstrom and with the diagonal distances being 4.156-4.165 angstrom. Four intramolecular H-bonds between a terminal oxime (NOH) group and the adjacent phenolate oxygen atom of another ligand stabilize the structure of the cluster. Spectral, magnetic, and cyclic voltammetry studies corroborate a stable Mn (III) tetramer.

Unexpected metal-promoted transformation yields an anthrylmethyl spiroanthracene - Kumbhar, Anupa A.; Kumbhar, Avinash S.; Puranik, Vedavati G. (Journal of Organic Chemistry, 2008)
The isolation and characterization of an unusual spiroanthracene, from the reaction of bisdichlororuthenium(II)bi-pyridine dihydrate with 3-(9-anthrylmethyl)pentane-2,4-dione (AMPD), is reported. This metal-promoted formation of spiroanthracene has been obtained for the first time during the synthesis of metal complexes.

Use of enantiomerically pure 7-azabicyclo[2.2.1]heptan-2-ol as a chiral template for the synthesis of aminocyclitols - Pandey, Ganesh; Tiwari, Keshri Nath; Puranik, Vedavati G. (Organic Letters, 2008)
Using enantiopure 7-azabicyclo[2.2.1]heptane-2-ol, the synthesis of cis- as well as trans-2-aminocyclohexanols, dihydroconduramine E-1, and ent-conduramine F-1 has been described.

Use of the pictet-spengler reaction for the synthesis of 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines and 1,4-disubstituted-beta-carbolines: formation of gamma-carbolines - Kusurkar, Radhika S.; Alkobati, Nabil A. H.; Gokule, Anita S.; Puranik, Vedavati G. (Tetrahedron, 2008)
Microwave-assisted conjugate addition of indole on nitro-olefins furnished nitro compounds, which were reduced to tryptamines. Further, by using Pictet-Spengler condensation, new 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines were synthesized in diastereoselective manner. Dehydrogenation of the tetrahydro-beta-carbolines produced new 1,4-disubstituted-beta-carbolines. As a new observation, in some of the cases, Pictet-Spengler condensation and dehydrogenation gave two products, namely 1,4-disubstituted-beta-carbolines and 1,4-disubstituted-gamma-carbolines. A mechanism is proposed for this observation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3; 4-Disubstituted-1; 4-disubstituted-beta-carboline; 4-disubstituted-gamma-carboline; 4-tetrahydro-beta-carboline; 4-tetrahydro-gamma-carboline; Pictet-Spengler reaction

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions

2-(2,6-Dimethoxyphenyl)-5-hydroxy-7-methoxy-4H-1-benzopyran-4-one - Kumar, R. Ravi; Krishnaiah, M.; Kumar, N. Jagadesh; Reddy, D. Gunasekhar; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2009)
In the title compound, C18H16O6, the dimethoxyphenyl ring is rotated by 61.8 (1)degrees from the plane of the benzopyran system. The molecule is stabilized by an intramolecular O-H center dot center dot center dot O hydrogen bond.

Combinatorial library of primaryalkylammonium dicarboxylate gelators: a supramolecular synthon approach - Sahoo, Pathik; Adarsh, N. N.; Chacko, George E.; Raghavan, Srinivasa R.; Puranik, Vedavati G.; Dastidar, Parthasarathi (Langmuir, 2009)
Following the supramolecular synthon approach, a combinatorial library comprising 35 organic salts derived from 7 dicarboxylic acids (malonic, succinic-, adipic, L-tartaric-, maleic-, phthalic-, and isophthalicacid) and 5 primaryalkyl amines Me-(CH2)(n)-NH2 (n = 11 - 15) was prepared and scanned for gelation. About 66% of the salts in the combinatorial library were found to show moderate to good gelling ability in various polar and nonpolar solvents including commercial fuels such as petrol. The majority of the salts having a rigid, unsaturated anionic backbone (maleate, phthalate, and isophthalate) did not show gelation; only the corresponding hexadecylammonium salts showed gelation. Some of the representative gels were characterized by rheology, small-angle neutron scattering (SANS), optical microscopy (OM), and scanning electron microscopy (SEM). Single-crystal structures of two gelator and two nongelator salts were also discussed in the context of supramolecular synthon and structure-property correlation.

Diethyl [(5-chloro-2-hydroxyanilino)(4-chlorophenyl)methyl]phosphonate - Krishnaiah, M.; Babu, V. H. H. Surendra; Prasad, G. Syam; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2009)
In the title compound, C17H20Cl2NO4P, the P atom is bonded in a distorted tetrahedral environment. The dihedral angle between the two benzene rings is 80.5 (1)degrees. In the crystal structure, intermolecular O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds link pairs of molecules into centrosymmetric dimers. These dimers, are in turn, linked by weak intermolecular C-H center dot center dot center dot O hydrogen bonds into one-dimensional chains along [010]. Additional stabilization is provided by very weak C-H center dot center dot center dot Cl interactions.

First ionic liquid-promoted Kabbe condensation reaction for an expeditious synthesis of privileged bis-spirochromanone scaffolds - Muthukrishnan, Murugan; Basavanag, U. M. V.; Puranik, Vedavati G. (Tetrahedron Letters, 2009)
A variety of privileged bis-spirochromanones were synthesized for the First time from 4,6-diacetyl resorcinol in one-pot by carrying out the Kabbe condensation in loom temperature ionic liquid [bbim]Br. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bis-spirochromanone; Ionic liquid; Kabbe condensation; Morpholine

Highly diastereoselective 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate: synthesis of polyhydroxylated perhydroazaazulenes - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2009)
An intermolecular 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate was found to be perfectly diastereoselective at the nitrone carbon to give exclusive formation of isoxazolidine. The N-O bond reductive cleavage in isoxazolidine followed by lactam reduction afforded a pyrrolidine ring skeleton with sugar appendage that on acetonide cleavage and reductive amino-cyclization gave hitherto unknown hydroxymethyl-substituted hexa- and pentahydroxy perhydroazaazulenes.
Keywords: 1; 3-dipolar nitrone olefin cycloaddition (DNOC); diastereoselectivity; Iminosugars; inhibitors; nitrone

NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Stereoselective synthesis of (+)-isoindolo-beta-carboline - Wakchaure, Prasad B.; Puranik, Vedavati G.; N. P. Argade (Tetrahedron-Asymmetry, 2009)
Starting from homophthalic anhydride and (S)-tryptophan, the stereoselective synthesis of (+)-isoindolo-beta-carboline has been described via the corresponding homophthalimide, its chemoselective oxidative ring contraction, and the intramolecular dehydrative ring closure followed by a geometry-specific demethoxycarbonylation. (C) 2009 Elsevier Ltd. All rights reserved.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.

Effect of the allylic substituents on ring closing metathesis: the total synthesis of stagonolide B and 4-epi-stagonolide B - Giri, Awadut G.; Mondal, Mohabul A.; Puranik, Vedavati G.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2010)
The total syntheses of stagonolide B and its 4-epimer were carried out to probe into how the relative stereochemistry of allylic hydroxy groups and their protecting groups influence the efficiency of the ring closing metathesis.

General and concise asymmetric synthesis of sphingosine, safingol and phytosphingosines via tethered aminohydroxylation - Kumar, Pradeep; Dubey, Abhishek; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2010)
A novel, practical and efficient enantioselective synthesis of sphingoid bases, L-threo-[2S,3S]-sphinganine (safingol), L-threo-[2S,3S]-sphingosine, L-arabino-[2R,3S,4R] and L-xylo-[2R,3S,4S]-C(18)-phytosphingosine is described. The synthetic strategy features the Sharpless kinetic resolution and tethered aminohydroxylation (TA) as the key steps.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran

Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.

1,8-Bis(4-methoxy-3-nitrophenyl)naphthalene - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2011)
Molecules of the title compound, C(24)H(18)N(2)O(6), are located on a twofold rotation axis passing through through the central C-C bond of the naphthalene ring system. The molecular conformation is characterized by a roughly coplanar arrangement of the two substituted phenyl rings [dihedral angle 18.53 (5)degrees]. These two aryl rings are each twisted by 65.40 (5)degrees from the plane of the naphthyl unit.

Bicyclic amino acid-carbohydrate-conjugates as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres - Kale, Sangram S.; Chavan, Sanjay T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes a general synthetic route to bicyclic amino acid-carbohydrate-conjugates, which would be useful as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres. The synthesis was achieved in 12 steps starting from D-glucose. The striking features of this system are the bicyclic rigid core displaying an a-amino acid side chain and hydroxyethylamine moiety - both of which would be potentially important for receptor interactions, leading to various biomedical responses, as described in the literature. Crystal structure investigation suggested extensive intermolecular hydrogen-bonding interactions in this system, involving the backbone amide and hydroxyl groups.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Diastereoselective synthesis of 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines via glacial acetic acid catalyzed pictet - spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Arkivoc, 2011)
The Pictet-Spengler reaction of substituted tryptamines with cyclic ketones using glacial acetic acid afforded only one diastereomer of unreported 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines. The stereoselectivity in the reaction has been demonstrated using unsymmetrical ketones and single-crystal X-ray analysis of one of the spiro products in the form of base, its sulfate and hydrochloride salts, which indicated the formation of only the R, R diastereomer.
Keywords: 1; 3; 4; 4-Trisubstituted-2; 9-tetrahydrospiro-beta-carbolines; beta-substituted tryptamine; Diastereoselective Pictet-Spengler reaction; Glacial acetic acid

Diastereoselective synthesis of tetrasubstituted-octahydro-3,6-diazacarbazoles and tetrasubstituted-3,6-diazacarbazoles via double Pictet-Spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2011)
Pictet-Spengler condensation of 2,5-bis(2-phenyl-1-aminoethyl)pyrrole using glacial acetic acid afforded only one diastereomer of unreported tetrasubstituted-octahydro-3,6-diazacarbazoles. These were readily dehydrogenated to tetrasubstituted-3,6-diazacarbazoles. The stereoselectivity in the Pictet-Spengler reaction has been demonstrated using single crystal X-ray analysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 5-Bis(2-phenyl-1-aminoethyl)pyrrole; 6-diazacarbazoles; Diasteroselective Pictet-Spengler reaction; Glacial acetic acid; Tetrasubstituted-3; Tetrasubstituted-octahydro-3

Dibutyl phthalate, a secondary metabolite from mimusops elengi - Ruikar, A. D.; Gadkari, T. V.; Phalgune, U. D.; Puranik, Vedavati G.; Deshpande, N. R. (Chemistry of Natural Compounds, 2011)

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Facile synthesis of N-benzylated 3-alkyl-2,6-diarylpiperidin-4-ones: Stereochemical investigation by 1D/2D NMR and single-crystal XRD - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2011)
A series of thirteen 1-benzyl-3-alkyl-2,6-diarylpiperidin-4-ones 14-26 were conveniently synthesized in high yields 87-92%. In order to find the impact on piperidone stereochemistry, beside the N-benzylation, methyl/ethyl/isopropyl groups at C-3 and halo/alkyl/alkoxy/benzyloxy groups on the phenyl rings at C-2/C-6 were introduced. All the synthesized compounds were characterized by mass, (1)H and (13)C NMR spectral studies. Of them, the 1-benzyl-3-ethyl-2,6-diphenylpiperidin-4-one 22 was completely characterized by 2D NMR techniques such as (1)H-(1)H COSY, (1)H-(13)C COSY and NOESY to assign the signals, unambiguously. The proton coupling constants and NOE correlations provided the complete stereochemistry of 22, which is further witnessed by its single-crystal XRD analysis. The NMR and XRD studies revealed that the compound 22 exists in a chair conformation with equatorial orientation of all the substituents in both solution and solid states. On the basis of their vicinal coupling constants, the chair conformation with equatorial orientation of the substituents at C-2, C-3, C-6 and N is proposed for all compounds 14-26; moreover, a considerable population of boat conformation also suggested for the compound 26 along with the predominant chair conformation, in solution. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2D NMR; Conformation; N-benzylation; Piperidin-4-one; single-crystal XRD; Stereochemistry

Ferrocene based organometallic gelators: a supramolecular synthon approach - Sahoo, Pathik; Puranik, Vedavati G.; Patra, A. K.; Sastry, P. U.; Dastidar, Parthasarathi (Soft Matter, 2011)
The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH2)(n)-NH2 (n = 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffraction data in combination with optical-, scanning-, and transmission-electron microscopy reveals that the supramolecular synthon approach adopted herein for designing LMWGs is indeed useful and allows one to get an easy access to a new series of organometallic gelators.

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design

Phytochemical investigation of artemisia pallens - Ruikar, Anjali D.; Jadhav, Ravindra B.; Phalgune, Usha D.; Rojatkar, Supada R.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Helvetica Chimica Acta, 2011)
Two new eudesmanolides, pallensin (1) and 4-epipallensin (2), along with a known eudesmanolide, santonin, and a known flavone, 4-epivalgarin, have been isolated from the aerial part of A. pallens. Their structures were established by detailed spectral studies (1D and 2D) and by comparison of their spectroscopic data with those of known compounds.

Regio- and stereoselective selenium dioxide allylic oxidation of (E)-dialkyl alkylidenesuccinates to (Z)-allylic alcohols: synthesis of natural and unnatural butenolides - Patel, Ramesh M.; Puranik, Vedavati G.; N. P. Argade (Organic & Biomolecular Chemistry, 2011)
The first SeO(2) induced (Z)-selective allylic alcohol formation of dialkyl alkylidenesuccinates has been demonstrated to accomplish one-step syntheses of several essential butenolides and fused butenolides via an unusual E- to Z- carbon-carbon double bond isomerisation followed by the lactonization pathway. The observed regio- and stereoselective SeO(2) allylic oxidation protocol has also been extended to the diastereoselective total synthesis of bioactive natural product isomintlactone, its direct conversion to mintlactone and an example of the base-catalyzed intramolecular rearrangement of gamma-lactone to delta-lactone.

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

Synthesis, electronic structure, DNA and protein binding, DNA cleavage, and anticancer activity of fluorophore-labeled copper(II) complexes - Bhat, Satish S.; Kumbhar, Anupa A.; Heptullah, Hussain; Khan, Ayesha A.; Gobre, Vivekanand V.; Gejji, Shridhar P.; Puranik, Vedavati G. (Inorganic Chemistry, 2011)
Two mononuclear fluorophore-labeled copper(II) complexes [Cu(nip)(acac)](+) (2) and [Cu(nip)(2)](2+) (3), where fluorophore is 2-(naphthalen-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (nip) (1) and acac is acetylacetone, have been synthesized aid characterized by various techniques. The ligand 1 and complex 2 are structurally characterized by single-crystal X-ray diffraction. The coordination geometries around the copper are square planar in solid as well as solution state as evidenced by electron paramagnetic resonance (EPR) spectroscopy. The density functional calculations carried out on 1-3 have shown that electron-rich regions in the highest occupied orbital are localized on the naphthalene end partly on the phenanthroline moiety. Both complexes 2 and 3 in dimethyl sulfoxide (DMSO) exhibit near square planar structure around the metal ion in their ground state. Time-dependent density functional theory (TD-DFT) calculations reveal that Cu(II) ion in complex 2 shows tetrahedral coordination around the metal while 3 retains its square planar geometry in the lowest excited state. The interaction of complexes with calf-thymus DNA (CT DNA) has been explored by using absorption, emission, thermal denaturation, and viscosity studies, and the intercalating mode of DNA binding has been proposed. The complexes cleave DNA oxidatively without any exogenous additives. The protein binding ability has been monitored by quenching of tryptophan emission in the presence of complexes using bovine serum albumin (BSA) as model protein. The compounds showed dynamic quenching behavior. Further, the anticancer activity of the complexes on MCF-7 (human breast cancer), HeLa (human cervical cancer), HL-60 (human promyelocytic leukemia), and MCF-12A (normal epithelial) cell lines has been studied. It has been observed that 3 exhibits higher cytotoxicity than 2, and the cells undergo apoptotic cell death.

Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines

Synthesis of tetrahydro-5-azaindoles and 5-azaindoles using pictet-spengler reaction-appreciable difference in products using different acid catalysts - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron, 2011)
Pictet-Spengler condensation of 2-(aryl)-2-(1H-pyrrol-2-yl)ethanamines using conventional acid catalysts like TMSCl or TFA resulted in the formation of substituted 5-azaindoles involving a tandem one pot four steps reaction sequence. By contrast use of glacial acetic acid furnished the targeted tetrahydro-5-azaindoles in diastereoselective manner. These were readily dehydrogenated to 5-azaindoles. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 2-(Aryl)-2-(1H-pyrrol-2-yl)ethanamines; 4; 7-Disubstituted-5-azaindoles; 7-Disubstituted-tetrahydro-5-azaindoles; Diastereoselective Pictet-Spengler reaction

1-Benzoyl-3-[(2-benzylsulfanyl)phenyl]thiourea - Bhattacharjee, Tirtha; Gogoi, Prasanta; Puranik, Vedavati G.; Gawade, Rupesh L.; Barman, Pranjit (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
In the title compound, C21H18N2OS2, a strong intramolecular N-H center dot center dot center dot O hydrogen bond [N center dot center dot center dot O = 2.642 (3) angstrom] between the amide N atom and the benzoyl O atom forms an almost planar six-membered ring in the central part of the molecule. In the crystal, molecules are packed through weak N-H center dot center dot center dot S interactions. Intra- and intermolecular hydrogen bonds and van der Waals interactions are the stabilizing forces for the crystal structure.

Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.

Andrographolide inhibits osteopontin expression and breast tumor growth through down regulation of PI3 Kinase/Akt signaling pathway - Kumar, S.; Patil, H. S.; Sharma, P.; Kumar, D.; Dasari, Sreekanth; Puranik, Vedavati G.; Thulasiram, H. V.; Kundu, G. C. (Current Molecular Medicine, 2012)
Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis paniculata has been shown to inhibit breast cancer cell proliferation, migration and arrest cell cycle at G2/M phase and induces apoptosis through caspase independent pathway. Our experimental evidences suggest that Andro attenuates endothelial cell motility and tumor-endothelial cell interaction. Moreover, Andro suppresses breast tumor growth in orthotopic NOD/SCID mice model. The anti-tumor activity of Andro in both in vitro and in vivo model was correlated with down regulation of PI3 kinase/Akt activation and inhibition of pro-angiogenic molecules such as OPN and VEGF expressions. Collectively, these results demonstrate that Andro may act as an effective anti-tumor and anti-angiogenic agent for the treatment of breast cancer.
Keywords: Andrographolide; angiogenesis and breast tumor; migration; osteopontin; PI 3 kinase

Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.

Efficient total synthesis of calothrixin B - Bhosale, Shrikar M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient synthesis of calothrixin B (2) is demonstrated starting from 9H-carbazol-4-ol, having two one-pot reaction sequences as key steps. As a novel observation, DMF-methanol was shown to be a hydride donor for reduction of aldehyde to alcohol. Unexpectedly, nucleophilic substitution of benzyloxy by methoxy group was observed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Calothrixin B; CAN; DMF-methanol; Hydride donor

Formal synthesis of (-)-stemoamide using a useful epimerization at C-8 - Chavan, Subhash P.; Harale, Kishor R.; Puranik, Vedavati G.; Gawade, Rupesh L. (Tetrahedron Letters, 2012)
The formal synthesis of (-)-stemoamide was achieved starting from L-pyroglutamic acid. The key steps used are the allylation using BF3 center dot OEt2, ring closing metathesis, allylic oxidation and a novel epimerization at C8. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allylation; Allylic oxidation; Pyroglutamic acid; Ring closing metathesis; Stemoamide

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Larvicidal potential of mimusops elengi against aedes aegypti (L) and Culex quinquefasciatus (Say) - Ruikar, Anjali D.; Pawar, Pushpa V.; Sen, Avalokiteswar; Phalgune, Usha D.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Journal of Vector Borne Diseases, 2012)
Keywords: Aedes aegypti; Culex quinquefasciatus; larvicidal activity; Mimusops elengi

MOF with hydroxynaphthoquinone as organic linker: molecular structure of [Zn(Chlorolawsone)(2)(H2O)(2)] and thermogravimetric studies - Salunke-Gawali, Sunita; Kathawate, Laxmi; Puranik, Vedavati G. (Journal of Molecular Structure, 2012)
Zinc complexes as MOF with hydroxynaphthoquinone as organic linkers are synthesized and characterized. The complexes Zn-1; [Zn(lawsone)(2)(H2O)(2)]center dot 3H(2)O and Zn-2; [Zn(chlorolawsone)(2)(H2O)(2)]center dot H2O, where lawsone is 2-hydroxy-1,4-naphthoquinone and chlorolawsone is 3-chloro-2-hydroxy-1,4-naphthoquinone, serve as hosts for adsorbed water molecules. nu(c=O) shows shift towards lower frequencies similar to 25 cm(-1) in Zn-1 and similar to 35 cm(-1) in Zn-2 in FTIR spectra. (HNMR)-H-1 shows upfield shift in Zn-1 and downfield shift in Zn-2 to the benzenoid ring protons. Bathochromic shift has been observed to the charge transfer band in UV-visible spectra of both complexes. The mass loss of adsorbed water molecules have been observed <100 degrees C in thermogravimetric (TG) studies. Three adsorbed water molecules are present in Zn-1, while one in Zn-2. X-ray diffraction studies of Zn-2 show, distorted octahedral geometry around Zn(II). The two chlorolawsone ligands are in plane with the metal, while water molecules are trans to this plane. Formation of MOF has been observed in the synthesis of Zn-2 with chlorolawsone as organic linkers. The structure is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O hydrogen bonding H-bonding along with Cl center dot center dot center dot pi interactions to form a beautiful MOF architecture. Zn(II) atoms along with organic ligand form a tetramer via O-H center dot O interactions. The shortest Zn center dot center dot center dot Zn distance is 5.04 angstrom. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 3-Chloro-2-hydroxy-1; 4-naphthoquinone; MOF; Naphthoquinone; O-H center dot center dot center dot O hydrogen bonding; Vapochromic behavior; Zinc complexes

New synthetic route for 1,2-diketo compounds using unexpected C-C bond cleavage by PCC - Bhosale, Shrikar M.; Momin, Aadil A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient method has been established for the preparation of 1,2-diketones by unexpected C-C bond cleavage in 4-keto-2-hydroxy esters using pyridiniumchlorochromate (PCC). (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Diketones; C-C bond cleavage; PCC

Organocatalytic dynamic kinetic resolution via conjugate addition: synthesis of chiral trans-2,5-dialkylcyclohexanones - Pandey, Ganesh; Adate, Priyanka A.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2012)
A novel strategy of initiating an organocatalysed dynamic kinetic resolution (dr up to 99 : 1 and er up to 94 : 6) for the synthesis of chiral trans-2,5-dialkylcyclohexanones by an asymmetric conjugate addition of dimethyl malonate on to 6-substituted cyclohexenones is reported.

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Regio- and stereoselective synthesis of new substituted tetrahydrocarbazoles and carbazoles using diels-alder reactions - Hingane, Dattatray G.; Goswami, Shailesh K.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Synthetic Communications, 2012)
Diels-Alder reactions of 3-vinylindoles were carried out with methyl acrylate and N-phenylmaleimide as dienophiles under microwave conditions to furnish unreported tetrahydrocarbazoles regio- and stereoselectively in good yields. Further dehydrogenation resulted in new substituted carbazoles.
Keywords: Carbazoles; regio- and stereoselective Diels-Alder reactions; tetrahydrocarbazoles

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation

Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations - Kundu, Tanaya; Chowdhury, Abhishek Dutta; De, Dipanwita; Mobin, Shaikh M.; Puranik, Vedavati G.; Datta, Anindya; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
{An effective anion sensor, [Ru-II(bpy)(2)(H2L-)](+) (1(+)), based on a redox and photoactive {Ru-II(bpy)(2)} moiety and a new ligand (H3L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F-) and acetate (OAc-) ions. Crystal structures of the free ligand, H3L and [1](ClO4) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO4) shows that the benzimidazole N-H of H2L- is hydrogen bonded with the pendant carboxylate oxygen while the imidazole N-H remains free for possible hydrogen bonding interaction with the anions. The potential anion sensing features of 1(+) have been studied by different experimental and theoretical (DFT) investigations using a wide variety of anions, such as F-, Cl-, Br-, I-, HSO4-, H2PO4-, OAc- and SCN-. Cyclic voltammetry and differential pulse voltammetry established that 1(+) is an excellent electrochemical sensor for the selective recognition kof F- and OAc- anions. 1(+) is also found to be a selective colorimetric sensor for F- or OAc- anions where the MLCT band of the receptor at 498 nm is red shifted to 538 nm in the presence of one equivalent of F- or OAc- with a distinct change in colour from reddish-orange to pink. The binding constant between 1(+) and F- or OAc- has been determined to be logK = 7.61 or 7.88, respectively, based on spectrophotometric titration in CH3CN. The quenching of the emission band of 1(+) at 716 nm (lambda(ex) = 440 nm

Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Strong metal-metal coupling in mixed-valent intermediates [Cl(L)Ru(mu-tppz)Ru(L)Cl](+), L = beta-diketonato ligands, tppz=2,3,5,6-tetrakis(2-pyridyl)pyrazine - Kundu, Tanaya; Schweinfurth, David; Sarkar, Biprajit; Mondal, Tapan Kumar; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
Five diruthenium(II) complexes [Cl(L)Ru(mu-tppz)Ru(L)Cl](1-5) containing differently substituted beta-diketonato derivatives (1: L = 2,4-pentanedionato; 2: L = 3,5-heptanedionato; 3: L = 2,2,6,6-tetramethyl-3,5-heptanedionato; 4: L = 3-methyl-2,4-pentanedionato; 5: L = 3-ethyl-2,4-pentanedionato) as ancillary ligands (L) were synthesized and studied by spectroelectrochemistry (UV-Vis-NIR, electron paramagnetic resonance (EPR)). X-ray structural characterisation revealed anti (1, 2, 5) or syn (3) configuration as well as non-planarity of the bis-tridentate tppz bridge and strong d pi(Ru-II) -> pi*(pyrazine, tppz) back-bonding. The widely separated one-electron oxidation steps, (RuRuII)-Ru-II/(RuRuIII)-Ru-II and (RuRuIII)-Ru-II/(RuRuIII)-Ru-III, result in large comproportionation constants (K-c) of >= 10(10) for the mixed-valent intermediates. The syn-configurated 3(n) exhibits a particularly high K-c of 10(12) for n = 1+, accompanied by density functional theory (DFT)-calculated minimum Ru-N bond lengths for this (RuRuIII)-Ru-II intermediate. The electrogenerated mixed-valent states 1(+)-5(+) exhibit anisotropic EPR spectra at 110 K with average values < g > of 2.304-2.234 and g anisotropies Delta g = g(1)-g(3) of 0.82-0.99. Metal-to-metal charge transfer (MMCT) absorptions occur for 1(+)-5(+) in the NIR region at 1660 nm-1750 nm (epsilon approximate to 2700 dm(3) mol(-1) cm(-1), Delta nu(1/2) approximate to 1800 cm(-1)). DFT calculations of 1(+) and 3(+) yield comparable Mulliken spin densities of about 0.60 for the metal ions, corresponding to valence-delocalised situations (Ru-2.5)(2). Rather large spin densities of about -0.4 were calculated for the tppz bridges in 1(+) and 3(+). The calculated electronic interaction values (V-AB) for 1(+)-5(+) are about 3000 cm(-1), comparable to that for the Creutz-Taube ion at 3185 cm(-1). The DFT calculations predict that the (RuRuIII)-Ru-III forms in 12(+)-52(+) prefer a triplet (S = 1) ground state with Delta E (S = 0 - S = 1) similar to 5000 cm(-1). One-electron reduction takes place at the tppz bridge which results in species [Cl(L)Ru-II(mu-tppz(.-)) Ru-II(L)Cl](-) (1(.-)-3(.-), 5(.-)) which exhibit free radical-type EPR signals and NIR transitions typical of the tppz radical anion. The system 4(n) is distinguished by lability of the Ru-Cl bonds.

Supported copper triflate as an efficient catalytic system for the synthesis of highly functionalized 2-naphthol Mannich bases under solvent free condition - Dindulkar, Someshwar D.; Puranik, Vedavati G.; Jeong, Yeon Tae (Tetrahedron Letters, 2012)
Various heterogeneous catalysts (Lewis acid) have been prepared and screened for the synthesis of Betti bases in an attempt to reduce the environmental hazards associated with the conventional homogeneous Lewis acid system. And we found especially Cu(OTf)(2)center dot SiO2 catalyzes the three-component coupling of aldehyde, 2-naphthol, and alicyclic amine to generate Betti base with high efficiency under neat conditions without additional co-catalyst or additive in air. The reaction is not sensitive to water and occurs smoothly in water as well. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Betti bases; single-crystal XRD; Solvent-free; Supported copper triflate; Three-component coupling

Supramolecular synthon transferability and gelation by diprimary ammonium monocarboxylate salts - Das, Uttam Kumar; Puranik, Vedavati G.; Dastidar, Parthasarathi (Crystal Growth & Design, 2012)
Earlier studies revealed that primary ammonium dicarboxylate (PAD) salts possessed gelling ability, and many such salts displayed a 1D columnar hydrogen bonded network (observed in primary ammonium monocarboxylate (PAM) salts) on either side of the dicarboxylate end of the anion. In the present study, a new series of diprimary ammonium monocarboxyate (DPAM) salts have been prepared with the aim of achieving supramolecular synthon transferability (the same 1D columnar hydrogen PAM bonded network on either side of the diammonium cation) in these salts. Single crystal X-ray diffraction studies revealed that, in 47% of the DPAM salts, such supramolecular synthon transferability indeed took place. Some of the DPAM salts also showed gelation ability. The gels were characterized by DSC, rheology, electron microscopy, and atomic force microscopy. Structure property correlation using single crystal and powder X-ray diffraction data on a selected gel was also attempted.

Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one

Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.

Understanding the growth of micro and nano-crystalline AlN by thermal plasma process - Kanhe, Nilesh S.; Nawale, Ashok B.; Gawade, Rupesh L.; Puranik, Vedavati G.; Bhoraskar, S. V.; Das, Asoka K.; Mathe, Vikas L. (Journal of Crystal Growth, 2012)
We report the studies related to the growth of crystalline AlN in a DC thermal plasma reactor, operated by a transferred arc plasma torch. The reactor is capable of producing the nanoparticles of Al and AlN depending on the composition of the reacting gas. Al and AlN micro crystals are formed at the anode placed on the graphite and nano crystalline Al and AlN gets deposited on the inner surface of the plasma reactor. X-ray diffraction, Raman spectroscopy analysis, single crystal X-ray diffraction and TGA-DTA techniques are used to infer the purity of post process crystals as a hexagonal AlN. The average particle size using SEM was found to be around 30 mu m. The morphology of nanoparticles of Al and AlN, nucleated by gas phase condensation in a homogeneous medium were studied by transmission electron microscopy analysis. The particle ranged in size between 15 and 80 nm in diameter. The possible growth mechanism of crystalline AlN at the anode has been explained on the basis of non-equilibrium processes in the core of the plasma and steep temperature gradient near its periphery. The gas phase species of AlN and various constituent were computed using Murphy code based on minimization of free energy. The process provides 50% yield of microcrystalline AlN and remaining of Al at anode and that of nanocrystalline h-AlN and c-Al collected from the walls of the chamber is about 33% and 67%, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from high temperature solutions; Nitride; Semiconducting aluminum compound

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Antimycobacterial labdane diterpenes from leucas stelligera - Kulkarni, Roshan R.; Shurpali, Ketaki; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Journal of Natural Products, 2013)
Phytochemical investigation of the acetone extract of the aerial parts of Leucas stelligera afforded four new compounds (1-4) belonging to the labdane diterpene series as well as two known flavones, velutin (5) and chrysoeriol (6). Structure elucidation of the new compounds was carried out using ID and 2D NMR spectroscopic data and single-crystal X-ray crystallography of compound 1. Compounds 1-4 exhibited selective antimycobacterial activity against Mycobacterium tuberculosis with IC50 values in the range 5.02-9.80 mu g/mL.

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

New dipyranocoumarin from the leaves of calophyllum apetalum willd - Joshi, Swati P.; Kulkarni, Smita R.; Phalgune, Usha D.; Puranik, Vedavati G. (Natural Product Research, 2013)
A new dipyranocoumarin, -hydroxytomentolide A (1) was isolated from the leaves of Calophyllum apetalum together with the known compounds friedelin (2), apetalactone (3), inophyllum C (4) and canophyllol (5). The structure of the new compound was established by spectroscopic studies which include H-1 NMR, C-13 NMR, NOESY, HetCOSY, COLOC experiments and single crystal X-ray diffraction analysis.
Keywords: -hydroxytomentolide A; Calophyllum apetalum; dipyranocoumarins; Guttiferae; Triterpenoids

NHC-Catalyzed reaction of enals with hydroxy chalcones: diastereoselective synthesis of functionalized coumarins - Bhunia, Anup; Patra, Atanu; Puranik, Vedavati G.; Biju, Akkattu T. (Organic Letters, 2013)
The N-heterocyclic carbene-catalyzed annulation of enals with 2'-hydroxy chalcones afford cyclopentane-fused coumarin derivatives with an excellent level of diastereocontrol. The reaction tolerates a broad range of functional groups; 25 examples are given, and a preliminary mechanistic investigation is provided.

Orthanilic acid-promoted reverse turn formation in peptides - Kale, Sangram S.; Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2013)
Orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant), an aromatic beta-amino acid, has been shown to be highly useful in inducing a folded conformation in peptides. When incorporated into peptide sequences (Xaa-(S)Ant-Yaa), this rigid aromatic beta-amino acid strongly imparts a reverse-turn conformation to the peptide backbone, featuring robust 11-membered-ring hydrogen-bonding.

Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Synthesis and X-ray single crystal structure of a cadmium(II) acetophenone thiosemicarbazone complex and its use as a single-source precursor for the preparation of CdS nanocrystallites and thin films - Palve, Anil M.; Joshi, Pranaya V.; Puranik, Vedavati G.; Garje, Shivram S. (Polyhedron, 2013)
{A cadmium(II) acetophenone thiosemicarbazone complex has been prepared and characterized by elemental analysis, infrared and nuclear magnetic resonance (H-1 and C-13H-1) spectroscopic techniques. Its single crystal structure has also been determined. The compound is found to be monoclinic, space group C2/c, with a = 12.1020(3) angstrom
Keywords: CdS; Nanocrystallites; Single source precursor; Thin films; Thiosemicarbazone complex

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Additive induced capture of elusive polymorphs of conformationally flexible Sulfonamides/Sulfoesters - Shaikh, Samir Rashid; Gawade, Rupesh L.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Gonnade, Rajesh (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: additive induced polymorphism; intermolecular interactions; phase transition

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.

Design, synthesis and cytotoxicity of novel N-benzylpiperidin-4-one oximes on human cervical cancer cells - Dindulkar, Someshwar D.; Bhatnagar, Ira; Gawade, Rupesh L.; Puranik, Vedavati G.; Kim, Se-Kwon; Anh, Dong Hyun; Parthiban, Paramasivam; Jeong, Yeon Tae (Journal of Chemical Sciences, 2014)
A series of fifteen diversified N-benzylpiperidin-4-one oximes were synthesized and characterized by their NMR spectral data. Additionally, single-crystal XRD analysis was performed for the representative symmetrically and unsymmetrically substituted molecules. All the synthesized oximes from unsymmetrical ketones existed as E-isomer as witnessed by their NMR and XRD data. Among the synthesized target compounds that evaluated for their in vitro cytotoxicity against human cervical carcinoma (HeLa) cells, five compounds were potent with IC50 < 17 mu M. 1-Benzyl-2,6-bis(4-isopropylphenyl)-3-methylpiperidin-4-one oxime 3c with an IC50 of 13.88 mu M was found to be the best active compound as depicted by the microscopic analysis.
Keywords: Cytotoxicity; HeLa cells; N-benzylpiperidin-4-one oximes; single-crystal XRD

Divergent total synthesis of 1,6,8a-tri-epi-castanospermine and 1-deoxy-6,8a-di-epi-castanospermine from substituted azetidin-2-one (beta-lactam), involving a cascade sequence of reactions as a key step - Tiwari, Dipak Kumar; Bharadwaj, Kishor Chandra; Puranik, Vedavati G.; Tiwari, Dharmendra Kumar (Organic & Biomolecular Chemistry, 2014)
A divergent, short, and novel total synthesis of 1,6,8a-tri-epi-castanospermine (7) and 1-deoxy-6,8a-di-epi-castanospermine (8) has been developed via a common precursor, 15, obtained from D-mannitol derived beta-lactam. The key step involves a one pot cascade sequence of trimethyl sulfoxonium ylide based cyclization of epoxy sulfonamide 14 via epoxide ring opening, one carbon homologation followed by intramolecular cyclization.

Formation of a pseudo-beta-hairpin motif utilizing the Ant-Pro reverse turn: consequences of stereochemical reordering - Nair, Roshna V.; Kotmale, Amol S.; Dhokale, Snehal A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2014)
Herein, we report a special case of pseudo-beta-hairpin formation by tetrapetide sequences featuring a two-membered Ant Pro dipeptide motif (Ant = anthranilic acid and Pro = proline) at the loop region. These folded structures uniquely feature the presence of C9- and C17-H-bonding patterns at reverse turn and interstrand regions, respectively. Their hairpin nucleation and folding propensities have been expounded using solution and solid state studies of distinct stereochemically altered sequences.

Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide

Monitoring cellular uptake and cytotoxicity of copper(II) complex using a fluorescent anthracene thiosemicarbazone ligand - Kate, Anup N.; Kumbhar, Anupa A.; Khan, Ayesha A.; Joshi, Pranaya V.; Puranik, Vedavati G. (Bioconjugate Chemistry, 2014)
The thiosemicarbazone derivative of anthracene (ATSC, anthracene thiosemicarbazone I) and its copper(II) complex (CuATSC, 2) were synthesized and characterized by spectroscopic, electrochemical, and crystallographic techniques. Interaction of 1 and 2 with calf thymus (CT) DNA was explored using absorption and emission spectral methods, and viscosity measurements reveal a partial-intercalation binding mode. Their protein binding ability was monitored by the quenching of tryptophan emission using bovine serum albumin (BSA) as a model protein. Furthermore, their cellular uptake, in vitro cytotoxicity testing on the HeLa cell line, and flow cytometric analysis were carried out to ascertain the mode of cell death. Cell cycle analysis indicated that 1 and 2 cause cell cycle arrest in sub-G1 phase.

Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Reaction between lawsone and aminophenol derivatives: synthesis, characterization, molecular structures and antiproliferative activity - Kathawate, Laxmi; Joshi, Pranya V.; Dash, Tapan Kumar; Pal, Sanjima; Nikalje, Milind; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Reaction between two bioreductive reactants lawsone (2-hydroxy-1,4-napthoquinone) and derivatives 2-aminophenol without catalyst is reported. The reaction between lawsone and 4-chloro-2-aminophenol leads to formation of red colored major product 1A:[2-[(5-chloro-hydroxyphenyl)amino]naphthalene-1,4-dione] and fluorescent orange colored minor compound 1B:[10-chloro-benzo[alpha]phenoxazine-5-one]. Molecular structure of 1A and 1B were determined by single crystal X-ray diffraction. Two mechanisms were proposed to the formation of red 1A and 1B. `Ortho-para' tautomeric equilibrium was observed in DMSO-d(6) solution in 1A, which was revealed by H-1, C-13 NMR and LC-MS studies. Molecules of 1A formed dimers via N-H center dot center dot center dot O interaction and polymeric chain of dimers was formed by OH center dot center dot center dot O interactions. Cl center dot center dot center dot Cl interactions were observed between the polymeric chains of dimers in 1A. Molecules of 1B show Cl center dot center dot center dot N interaction. Antiproliferative properties is studied for 1A-5A compounds (obtained by the reaction of lawsone with 2-amino-4-methylpheno1;2A, 2-aminopheno1;3A, 3-aminophenol;4A and 4-aminophenol;5A) and evaluated against two cancer cell lines, THP1 (human monocytic leukemia cells) and COLO205 (colorectal adenocarcinoma) and one normal cell line, HEK293T (human embryonic kidney). The values of 50% inhibitory concentration (IC50) of compounds 1A-5A was determined using XTT assay. The cytotoxic effects of compounds 2A and 3A were observed against COLO205 and compounds 4A and 5A on THP1 were observed to be higher in comparison to their effect on HEK293T cell lines. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Aminophenol; Benzo[alpha]phenoxazine; Cl center dot center dot center dot N interactions; Lawsone; pi-pi stacking interaction

Synthesis, characterization, and crystal structure determination of palladacycles of para-substituted 2-thiobenzylazobenzenes - Bhattacharjee, Tirtha; Kalita, Mukul; Chakravarty, Debamitra K.; Barman, Pranjit; Puranik, Vedavati G. (Journal of Coordination Chemistry, 2014)
Bichelated neutral palladacycles (1-3), [Pd(L)Cl], were synthesized from reaction of the new potential tridentate (C,N,S) ligands, 2-thiobenzylazobenzene (L-1), 4'-methyl-2-thiobenzylazobenzene (L-2), and 4'-chloro-2-thiobenzylazobenzene (L-3) with sodium tetrachloropalladate(II), Na-2[PdCl4], in ethanol. The compounds were characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible, and thermogravimetric analysis. The crystal structures of L-2 and 1-3 were determined by single-crystal X-ray diffraction. In 1-3, the geometry around palladium remains almost square planar, coordinated to carbon, nitrogen, and sulfur of the ligand forming a bichelated cyclopalladate complex. The C-H center dot center dot center dot Cl type intermolecular hydrogen bonds, weak pi center dot center dot center dot pi, C-H center dot center dot center dot pi, and van der Waals interactions are believed to be the stabilizing forces for the crystal packing of these palladacycles.
Keywords: 2-Thiobenzylazobenzene; CNS-donor ligand; crystal structure; Palladacycles; Thermogravimetric analysis

Synthesis, characterization and molecular structures of homologated analogs of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone - Salunke-Gawali, Sunita; Pawar, Omkar; Nikalje, Milind; Patil, Rishikesh; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath (Journal of Molecular Structure, 2014)
Four analogues of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone (where n-alkyl is methyl in L-1Br, ethyl in L-2Br, propyl in L-3Br and butyl in L-4Br) are synthesized and characterized. A reaction mechanism is proposed for the formation of L-1 Br to L-4Br from the starting material 2,3-dibromo-1,4-naphthoquinone. The v(N-H) frequency in the FT-IR spectra is affected by the intramolecular hydrogen bonding in L-1Br to L-4Br and is observed similar to 3267 cm(-1) in L-2Br. A shift of similar to 25 cm(-1) is observed in the v(C-Br) frequency in all the compounds as compared to 2,3-dibromo-1,4-naphthoquinone (627 cm(-1)). A broad charge transfer band is observed between 400 and 600 nm in the UV-Vis spectra, which imparts red colour to all the compounds. Molecular structures of L-2Br and L-3Br were studied by single crystal X-ray diffraction studies. Molecules of L-2Br crystallize in Pca2(1), whereas the molecule L-3Br crystallizes in the P-1 space group. Molecules of L-2Br forms a polymeric chain through N-H...O interaction and forms beautiful butterfly like arrangement of molecules when viewed down the `a' axis. Ladder like polymeric chain of molecules is observed in L-3Br via C-H...O and N-H...O interactions. Every alternating neighbouring chains of L-3Br, show pi-pi stacking interactions between the quinonoid rings of the molecules, however this interaction is not observed in L-2Br. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Dibromo-1; 4-naphthoquinone; Aminonaphthoquinone; hydrogen bonding; Michael addition; pi-pi stacking

Synthesis, spectroscopic characterization and structural investigations of new adduct compound of carbazole with picric acid: DNA binding and antimicrobial studies - Saravanabhavan, Munusamy; Sathya, Krishnan; Puranik, Vedavati G.; Sekar, Marimuthu (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
Carbazole picrate (CP), a new organic compound has been synthesized, characterized by various analytical and spectroscopic technique such as FT-IR, UV-Vis, H-1 and C-13 NMR spectroscopy. An orthorhombic geometry was proposed based on single crystal XRD study. The thermal stability of the crystal was studied by using thermo-gravimetric and differential thermal analyses and found that it was stable up to 170 degrees C. Further, the newly synthesized title compound was tested for its in vitro antibacterial and antifungal activity against various bacterial and fungal species. Also, the compound was tested for its binding activity with Calf thymus (CT) DNA and the results show a considerable interaction between CP and CT-DNA. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity and DNA-interaction; CP adduct; Single crystal XRD; TG-DTA

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Targeting a chemorefractory COLO205 (BRAF V600E) cell line using substituted benzo[alpha]phenoxazines - Pal, Sanjima; Konkimalla, V. Badireenath; Kathawate, Laxmi; Rao, Soniya S.; Gejji, Shridhar P.; Puranik, Vedavati G.; Weyhermueller, Thomas; Salunke-Gawali, Sunita (RSC Advances, 2015)
Mutational activations of the oncogene BRAF (especially BRAF V600E) result in a poor prognosis for colon cancer patients and are associated with chemoresistance rendering them refractory to treatment. The development of novel bioactive compounds with specific targeting abilities under such conditions is an urgent need in drug discovery. In this report we synthesize and characterize three fluorescent benzo[alpha]phenoxazine compounds (10R-benzo[alpha]phenoxazine-5-one, 1B; R = Cl, 2B; R = CH3, 3B; R = H) and their anticancer activities are evaluated in a COLO205 cell line. All three compounds with a log P value around 2 were cell permeable. However, 2B and 3B showed specific cytotoxicity in a malignant COLO205 cell line with a BRAF mutation (V600E) in comparison to a non-malignant wild-type BRAF HEK293T cell line. From further cell-based assays (cell cycle analysis, DNA fragmentation and caspase activation), we conclude that 2B and 3B treatment-induced selective cell death by inducing cell cycle arrest at the G0/G1 phase and caspase-mediated apoptosis (activation of the intrinsic and extrinsic pathways) are present only in BRAF V600E COLO205 cells. Further studies in the drug discovery pipeline might help develop these benzo[alpha]phenoxazines as promising chemotherapeutics for such refractory mutated cancers.

4 `-Epi-DNA: A DNA Mimic Containing 4 `-hydroxymethyl-alpha-l-Xylo-thymidine with compact backbone like RNA - Bagmare, Seema; Puranik, Vedavati G.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Nucleosides Nucleotides & Nucleic Acids, 2016)
Synthesis of C4-epi-DNA containing 3 5 linkages is reported for the first time. Crystal structure study of the monomer indicated that though the dihedral angle O3-C3-C4-C5 in this case would be like in RNA, the sugar conformation would remain like that in DNA. The study of the effect of this backbone configuration in DNA with respect to its binding to cDNA and RNA is reported in this note.
Keywords: 4 `-hydroxymethyl nucleosides C4 `-epi-DNA; Antisense Oligonucleotide

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae

4-Phenyl quinoline derivatives as potential serotonin receptor ligands with antiproliferative activity - Joshi, Pranaya V.; Sayed, Alim A.; RaviKumar, Ameeta; Puranik, Vedavati G.; Zinjarde, Smita S. (European Journal of Medicinal Chemistry, 2017)
Antagonists of signaling receptors are often effective non-toxic therapeutic agents. Over the years, there have been evidences describing the role of serotonin or 5-hydroxytryptamine (5-HT) in development of cancer. Although there are reports on the antiproliferative effects of some serotonin receptor antagonists, there are very few investigations related to understanding their structure-activity relationships. In this study, we report the screening of a library of 4-phenyl quinoline derivatives for their antiproliferative activities. Preliminary docking studies indicated that these ligands had the ability to bind to two of the serotonin. receptors, 5-HT1B and 5-HT2B. The results of the in silico experiments were validated by performing in vitro studies on MCF-7 breast cancer cell line. The ethylpiperazine derivatives showed maximum toxicity against this cancer cell line. The compounds inhibited Calcium ion efflux (induced by serotonin) and ERK activation. One of the most active 4-phenyl quinoline derivatives (H3a) also induced apoptosis, thereby, suggesting the use of this scaffold as a potential anticancer drug. (C) 2017 Elsevier Masson SAS. All rights reserved.

Vanadium-based polyoxometalate complex as a new and efficient catalyst for phenol hydroxylation under mild conditions - Sharma, Mitu; Saikia, Gangutri; Ahmed, Kabirun; Gogoi, Sandhya Rani; Puranik, Vedavati G.; Islam, Nashreen S. (New Journal of Chemistry, 2018)
An eco-compatible catalytic protocol for H2O2 induced hydroxylation of phenol (PH) to catechol (CT) and hydroquinone (HQ) in aqueous medium, using a polyoxovanadate (POV) complex as the catalyst, is described. The synthesis of the POV catalyst, with a new type of three dimensional framework, Na6(H2O)22(V10O28)2H2O (1) was accomplished by establishing a non-hydrothermal one-step methodology under mild conditions. The catalyst was characterized by elemental analysis, spectral studies, single crystal X-ray diffraction studies, and Brunauer–Emmett–Teller (BET) and TGA analysis. Under optimum conditions of reaction, conducted at ambient temperature, the phenol conversion reached up to 55.4% providing a TON of 138. The catalyst could be recovered easily and recycled at least up to three cycles without significant change in activity. The developed methodology is operationally simple and free from halogenated solvents or any other hazardous additives.

Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1

General and concise asymmetric synthesis of sphingosine, safingol and phytosphingosines via tethered aminohydroxylation (vol 8, pg 5074, 2010) - Kumar, Pradeep; Dubey, Abhishek; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2020)

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.

Reactions of 2,3-dibromonaphthalene-1,4-dione and pyridyl amines: X-ray structures, DFT investigations, and selective detection of the Hg2+ and Ni2+ ions - Aggrwal, Gunjan; Salunke-Gawali, Sunita; Gejji, Shridhar P.; Nikalje, Milind; Chakravarty, Debamitra; Verma, Prakash L.; Gosavi-Mirkute, Prajkta; Harihar, Shital; Jadhav , Mahesh; Puranik, Vedavati G. (Engineered Science, 2021)
<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">In this work, the products formed by the reaction between 2,3-dibromonaphthalene-1,4-dione with (pyridine-2-yl)methanamine and (pyridine-4-yl)methanamine are discussed in detial. The products 2-amino-3-bromonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) and 2-aminonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">B(1)<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) obtained are characterized through 1H and 13C-NMR, FTIR, mass spectrometry, single-crystal X-ray diffraction experiments, which are in conjunction with wB97X based density functional theory. <span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">compound <span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);"> can effectively and selectively detect Hg2+ and Ni2+ ions, and proposes a potential mechanism of action<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">.